Hypotension in normotensive pregnant women treated with nifedipine as a tocolytic drug - Luewan S. (2014)
Objective: To determine hypotensive effect of nifedipine in the treatment of preterm labor. Methods: A descriptive analytic study was conducted on pregnant women treated with nifedipine as tocolytic drug for preterm labor. Maternal blood pressure before and at 15, 30, 45 and 60 min after administration of nifedipine was evaluated and analyzed. Hypotension was defined as a decrease in systolic or diastolic blood pressure of 15 mmHg or more. Results: A total of 157 pregnant women met the inclusion criteria. The mean systolic and diastolic blood pressure before treatment was 109.4 and 72.5 mmHg, respectively. The blood pressure following treatment with nifedipine was significantly decreased both systolic and diastolic blood pressure (p < 0.05) at 30, 45 and 60 min. Of 157 patients, 28 (17.8%) and 27 (17.2%) had systolic and diastolic hypotension, respectively. Of the patients with decreased blood pressure, the mean decrease of systolic and diastolic blood pressure was 16.3 and 14.5 mmHg, respectively. Conclusion: Nifedipine was associated with a minimal but significant decrease in blood pressure. 17% of cases have hypotension. However, hypotension secondary to nifedipine was not associated with significant clinical symptoms, suggesting that nifedipine is relatively safe in terms of hypotensive effect. © Springer-Verlag 2010.